Predicting kinetics of polymorphic transformations from structure mapping and coordination analysis - Stevanovic, Vladan; Trottier, Ryan; Therrien, Felix; Musgrave, Charles; Holder, Aaron; Graf, Peter (arXiv.org, 2017)
To extend rational materials design and discovery into the space of metastable polymorphs, rapid and reliable assessment of their lifetimes is essential. Motivated by the early work of Buerger (1951), here we investigate the routes to predict kinetics of polymorphic transformations using solely crystallographic arguments. As part of this investigation we developed a general algorithm to map crystal structures onto each other and construct transformation pathways between them. The developed algorithm reproduces reliably known transformation pathways and reveals the critical role that the dissociation of chemical bonds along the pathway plays in choosing the best (low-energy barrier) mapping. By utilizing our structure-mapping algorithm we were able to quantitatively demonstrate the intuitive expectation that the minimal dissociation of chemical bonds along the pathway, or in ionic systems, the condition of coordination of atoms along the pathway not decreasing below the coordination in the end compounds, represents the requirement for fast transformation kinetics. We also demonstrate the effectiveness of the structure-mapping algorithm in combination with the coordination analysis in studying transformations between polymorphs for which a detailed atomic-level picture is presently elusive.